2013
DOI: 10.1212/wnl.0b013e31827e07be
|View full text |Cite
|
Sign up to set email alerts
|

New NBIA subtype

Abstract: MPAN is caused by mutations in C19orf12 leading to NBIA and prominent, widespread Lewy body pathology. The clinical phenotype is recognizable and distinctive, and joins pantothenate kinase-associated neurodegeneration and PLA2G6-associated neurodegeneration as one of the major forms of NBIA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
173
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(184 citation statements)
references
References 9 publications
10
173
0
1
Order By: Relevance
“…This can be easily pictured by T2-weighted magnetic resonance imaging (MRI). In the two large case series (Hartig et al, 2011;Hogarth et al, 2013), all 47 MPAN cases showed increased iron deposition in the globus pallidus, and all but two also had iron deposition in the substantia nigra. Noteworthy, one of these 47 patients showed an "eye of the tiger" sign, which is otherwise considered pathognomonic for PKAN.…”
Section: Neuroimagingmentioning
confidence: 97%
See 2 more Smart Citations
“…This can be easily pictured by T2-weighted magnetic resonance imaging (MRI). In the two large case series (Hartig et al, 2011;Hogarth et al, 2013), all 47 MPAN cases showed increased iron deposition in the globus pallidus, and all but two also had iron deposition in the substantia nigra. Noteworthy, one of these 47 patients showed an "eye of the tiger" sign, which is otherwise considered pathognomonic for PKAN.…”
Section: Neuroimagingmentioning
confidence: 97%
“…Until now, 67 MPAN patients have been described in the literature (Deschauer et al, 2012;Dezfouli et al, 2013;Dogu et al, 2012;Goldman et al, 2013;Hartig et al, 2011;Hogarth et al, 2013;Panteghini et al, 2012;Schottmann, Stenzel, Lutzkendorf, Schuelke, & Knierim, 2013;Schulte et al, 2013). A compilation of all these cases shows that MPAN leads to a distinctive phenotype with prominent pyramidal and extrapyramidal signs, cognitive decline, neuropsychiatric abnormalities, optic atrophy, and motor axonal neuropathy (Table 3.1).…”
Section: Clinical Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The list of NBIAs is continuously expanding. Besides PKAN caused by mutations in the PANK2 gene, [1,2] the best characterized subtypes include MPAN with mutations/deletions in the c19orf12 gene, [7][8][9] the PLA2G6 Associated Neurodegeneration (PLAN) with mutations in the PLA2G6 gene, [10] the Coasy Protein Associated Neurodegeneration (CoPAN) with mutations in the Coasy gene, [11] and the Beta-Propeller Protein Associated Neurodegeneration (BPAN) with mutations in the WDR45 gene. [12] A shared feature of these diseases is brain iron accumulation that is likely secondary to abnormalities in lipid metabolism and autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…This deletion results in an early stop codon (p. Gly69Arg fsTer10) and has been previously reported. [7][8][9] Brain magnetic resonance imaging (MRI) of the parents was subsequently ordered on a 3 Tesla Philips scanner, which revealed increased iron in the globus pallidus on T2-Fast Field Echo (FFE) scans in the 62 years old mother's but not in the 64 years old father's brain (see Figure 2). …”
Section: Geneticsmentioning
confidence: 99%